ANALYSIS OF MUI FATWA AND MINISTRY OF TRADE POLICY ON BOYCOTT PRODUCTS IN INDONESIA - Khurun'in Zahro'; Fadhila Sukur Indra; Yunita Wulandari; Siti Nur Adila; Maritza Putri Nabila (Islamic Economics Program, Faculty of Islamic Economics and Business, 2024)
The prolonged conflict between Palestine and Israel has made several parties more aggressively support Palestine. One form of Indonesia's support for Palestine is the issuance of the Indonesian Ulema Council (MUI) fatwa No 83 of 2023 on the Law of Supporting the Palestinian Struggle. Unlike the MUI, the Ministry of Trade did not issue any decree regarding the prohibition of Israeli boycott products entering Indonesia, as long as they follow the applicable procedures. This research method uses a literature study to collect data and information from books, journals, articles, and related news. The purpose of this research is to analyze the fatwa of MUI and the Ministry of Trade regarding the boycott of Israeli products circulating in Indonesia, as well as the response and attitude of the community regarding this matter. The result of this research shows that the boycott of Israeli products is a form of indirect support of the Indonesian people, namely with the MUI fatwa, which urges as much as possible to avoid transactions and use of products affiliated with Israel and that support colonialism and Zionism. Unlike the MUI, the Ministry of Trade does not prohibit any product from circulating and being traded in Indonesia as long as it follows the applicable rules. This also has an impact on the decline of Indonesia's economic level. The Ministry of Commerce, MUI, and the governments concerned should clarify and affirm the decisions made regarding the Israeli boycott of products in Indonesia.